IMPLEMENTATION OF TPACK APPROACH TOWARD CRITICAL THINKING ABILITY AND COGNITIVE LEARNING OUTCOMES OF STUDENTS OF SMA NEGERI 1 JAKENAN ON ENVIRONMENTAL CHANGE MATERIAL - Khoiril, Dina; Nurwahyunani, Atip (BIOMA : Jurnal Ilmiah Biologi, 2024)
This study aims to determine the effect of implementing the TPACK approach to developing critical thinking skills and student learning outcomes. The design used in this research is Experimental (Quasi-experimental) with Non Equivalent Control Group Design. The research subjects consisted of 72 high school students who were divided into two homogeneous classes, namely 36 students in the control class and 36 students in the experimental class. Students in the control class were taught conventional learning and the experimental class was taught with the TPACK approach. The TPACK approach to critical thinking skills is sufficient. Learning with the TPACK approach is more effective in improving learning outcomes than conventional learning. The results of the tcount test in the experimental class were 63.375 and the ttable was 1.666 while the control class the tcount test results were 25.102 and the ttable was 1.666.